THE EFFECT OF VISUAL MEDIA ON STDENTS WRITING MASTERY OF PROCEDURE TEXT ( A STUDY AT THE X GRADE STUDENTS OF SMA NEGERI 1 SIBABANGUN) - S.Pd., M.Hum, ASRIANI HASIBUAN (JURNAL EDUCATION AND DEVELOPMENT, 2017)
The aim of this research is to find out: 1) To what extent is the application of visual media on studentsâ writing procedure text a study at the tenth grade students of SMA Negeri 1 Sibabangun. 2) To what extent  is the  studentsâ writing mastery of procedure text before and after using visual media a study at the tenth grade students of SMA Negeri 1 Sibabangun. 3) Whether there is significant effect of visual media on studentsâ writing mastery of procedure text a study at the tenth grade students of SMA Negeri 1 Sibabangun. In order to achieve the purpose of the research, the writer carried the quantitative approach by applying experimental research method with one group pre-test and post-test design. The population was all of the tenth grade students consist of 187 students. The writer used cluster sampling technique to get the sample consists of 30 students. The data was collected by using instrument namely observation sheet and essay test. In this research, the writer used observation sheet about the application of visual media on studentsâ writing procedure text, the mean score 3.2, and it was categorized âgoodâ. And then the writer used ttest in pre-test and post-test design formula. After calculating data, it was found that the mean score of students in pre-test was 59 and it is categorized âbadâ. While the mean score of students in post-test is 74 and it was categorized âgoodâ.  The result of  ttest bigger than ttable (10.63>2.05). It means that the hypothesis is accepted. It means, there is a significant effect of visual media on studentsâ writing mastery of procedure text at the tenth grade students of SMA Negeri 1 Sibabangun.